Pancho Villa : a biography - Rouverol, Jean. (Garden City, N.Y., Doubleday, 1972)
A biography of the turn-of-the-century Mexican outlaw who helped overthrow the Diaz government in the Revolution of 1910.
Bibliography: p. [207]-208.
Keywords: Villa, Pancho, -- 1878-1923 -- Juvenile literature; Villa, Pancho, -- 1878-1923.; Mexico -- History